Leadership Style, Entrepreneurial Orientation and Their Consequences: A Review Paper - Hieu Minh VU (Communications of International Proceedings, 2020)
Effective Leadership is important for the growth and survival of every organization. Entrepreneurial orientation dimensions of risk-taking, innovativeness, and proactiveness enable an entrepreneur to spot and exploit opportunities ahead of competitors. The author uses a critical literature review method to draw insight on leadership styles, entrepreneurial orientation, and their consequences. The review highlights the important role different leadership styles play in promoting business performance, organizational effectiveness, and growth. It was observed that role of entrepreneurial orientation (EO) dimensions of risk-taking and innovativeness to organizational success is relatively unclear and inconsistent. This is due to mixed findings that were reported by scholars. The author recommends that more studies should be conducted on entrepreneurial orientation by incorporating more antecedents and consequences.
Keywords: Leadership; transformational leadership; entrepreneurship; entrepreneurial orientation (EO).